Evaluation of Aphrodisiac Activity of Siddha Herbal Formulation Vithu Vagai Chooranam in Experimental Rats - Ganesh, I. Sundara (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Aphrodisiac agents are used to arouse sexual desire, sexual pleasure, or sexual behavior. Many synthetic drugs are available in the market for improving sexual function. Even though modern medicines are widely accessible, it has some ill effects. To combat these side effects, people turn to alternative medical practices to combat these side effects. In this regard, a study was performed to investigate the aphrodisiac potential of herbal formulation Vithu vagaichooranam (VVC) by mating behavior study in male Wistar rats. Materials and Methods: The test drug VVC at 70 mg/kg and 90 mg/kg, Sildenafil citrate as Standard (5 mg/kg, p.o) and vehicle control (1 mL/kg p.o) were administered orally to rats (n = 6 animals per group) for 14 days. On the 15th day, the sexual behavior of the experimental rats was observed in a dim light in specially designed cages. The mating behavior parameter of male rats in each group was recorded individually. Results: Oral administration of VVC at both doses significantly increased the frequencies of mount, intromission, ejaculation frequency, Anogenital sniffing, and genital grooming (P < 0.001) when compared to the control and standard drug. The latencies of mount and intromission were significantly reduced and ejaculation latency was prolonged. Conclusion: The results of the study strongly suggested that the VVC has significant aphrodisiac potential in the above experimental model in male Wistar rats. Hence, in future, this formulation can be used as a potent stimulator of sexual behavior and an alternative for various sexual dysfunctions. The results thus support the therapeutic activity of this formulation claimed in the literature.